Lao PDR Economic Monitor, August 2019 : Maintaining Economic Stability - World Bank Group (World Bank, Vientiane, 2019)
Economic growth in Lao PDR is projected to rebound to 6.5 percent in 2019, up from 6.3 percent in 2018. This pick up is expected to be driven by growth of the construction sector supported by investments in large infrastructure projects, and a resilient services sector, led by wholesale and retail trade growth. The Government has remained committed to fiscal consolidation to contain public debt in the medium term by tightening public expenditure and improving revenue administration. The medium-term outlook remains broadly favorable, but subject to downside risks from heightened uncertainty in the global and domestic environments. Prolonged trade partners, and spillover to the domestic economy through lower trade and investment, and reduced prices for key export commodities. The authorities may face difficulty in responding to such economic shocks given the low level of foreign currency reserves and significant external public debt. A priority is therefore to create fiscal space through improving tax policy and administration as well as build up reserve buffers to respond to shocks. Additionally, improving the business environment and reversing the decline in the global ranking of the ease of doing business, particularly for small and medium-sized enterprises, could also contribute to greater macroeconomic stability, job creation and poverty reduction.